PEMANFAATAN BAHAN AJAR BERDASARKAN MULTI LEVEL REPRESENTASI UNTUK MELATIH KEMAMPUAN SISWA MENYELESAIKAN MASALAH KIMIA LARUTAN - Mujakir Mujakir (Lantanida Journal, 2017)
Obeservation results indicated that students have difficulty of explaining chemical phenomena in league level representations (macroscopic, symbolic, and submicroscopic levels). The aim of the study was to obtain the information related to the influence of the use of teaching materials based on multi-level representation of the ability to solve the problem of solution materials of MAN students in Pidie Jaya. The teaching material contained of macroscopic, symbolic, and submicroscopic levels. Type this of research was quasi experiment which was tested in MAN Pidie Jaya. The study was conducted for four months through two stages namely: (1) observasion, (2) implementation. Implementation was carried out by using one-group pre-test design and post-test design. Instruments used consist of; observation sheets, note sheets of learning constraints, assessment and problem solving and representation sheets, and student response questionnaires. The data were obtained them analyzed descriptively. The results showed: (1) the ability chemical problem solving in MAN Ulim Pidie Jaya was increased from the average of 43 pre-test to 73 in post-test result this means that the teaching materials based on multi level representation used can train the ability to solve problem the solution, (2) the profile of students' ability movement during the learning process using teaching materials based on multi level representation increased at one to three meetings, this happened because the fourth meeting material characteristic was more complex, (3) based on student response to the using of teaching materials based on multi level representation was very helpful in training solve chemical problems of solution.